Rendimento, valor nutritivo e características do dossel de cultivares de aveia-branca para silagem em diferentes alturas de corte - Klein, Arthur Pegoraro (2020)
Produce white oat silage is a great opportunity to use the idle agricultural area in the winter on Southern Region of Brazil. In addition to minimizing the risks to livestock activity, caused by weather conditions, silage has digestible nutrients similar to the original forage. The experiment was carried out in the Embrapa Trigo experimental field, in the Coxilha county, Rio Grande do Sul state, Brazil. The aim of the work was to evaluate whether there is intraspecific variability of white oats and of different cutting heights in terms of productivity, nutritional value, fermentative quality and canopy partition for whole plant silage. Eighteen cultivars of white oats were evaluated. Sowing, management and cultural treatments followed the protocol described for grain production as indicated by the culture. Plants were harvested with about dry matter (DM) concentration among 25 to 40% and ensiled in polyvinyl chloride (PVC) tubes. The variables analyzed were biomass yield, nutritional value (crude protein, fiber and estimated digestibility) by the near infrared reflectance method (NIRS), pH value and silage losses, as well as leaf, stem and panicle partition. UPFA Ouro cultivar was the highlight in yield with 10.6 t/ha in the cut at 10 cm and 9.1 t /ha in the cut at 20 cm. The increase in cutting height did not alter the crude protein, fiber and digestibility content estimated in most of the evaluated cultivars. The yield was reduced, on average, from 8.7 t/ha to 7.6 t/ha as the cutting height increased.